Nanocarriers for Cannabinoid Delivery: Enhancing Therapeutic Potential - Singh, Varun; Vihal, Samar; Rana, Rupali; Rathore, Charul (Recent Advances in Drug Delivery and Formulation, 2024)
Medical cannabis has potential therapeutic benefits in managing pain, anxiety, depression, and neurological and movement disorders. Phytocannabinoids derived from the cannabis plant are responsible for their pharmacological and therapeutic properties. However, the complexity of cannabis components, especially cannabinoids, poses a challenge to effective medicinal administration. Even with the increasing acceptance of cannabis-based medicines, achieving consistent bioavailability and targeted distribution remains difficult. Conventional administration methods are plagued by solubility and absorption problems requiring innovative solutions. After conducting a thorough review of research papers and patents, it has become evident that nanotechnology holds great promise as a solution. The comprehensive review of 36 research papers has yielded valuable insights, with 7 papers reporting enhanced bioavailability, while others have focused on improvements in release, solubility, and stability. Additionally, 19 patents have been analyzed, of which 7 specifically claim enhanced bioavailability, while the remaining patents describe various formulation methods. These patents outline effective techniques for encapsulating cannabis using nanocarriers, effectively addressing solubility and controlled release. Studies on the delivery of cannabis using nanocarriers focus on improving bioavailability, prolonging release, and targeting specific areas. This synthesis highlights the potential of nanotechnology to enhance cannabis therapies and pave the way for innovative interventions and precision medicine.
Keywords: Cannabis